Association between hematological parameters and metabolically unhealthy phenotypes in children and adolescents.: Asociación entre parámetros hematológicos y fenotipos metabólicamente poco saludables en niños y adolescentes - Horta-Baas, Gabriel José (2023)
Objective. Metabolic syndrome has been associated with changes in the composition of circulating blood cells. Hematologic indices can be used to identify the subjects at risk of metabolically unhealthy phenotype (MUP). This study investigated whether hematological indices can serve as biomarkers to distinguish metabolically healthy phenotype (MHP) from MUP in children and adolescents. Methods. Two hundred ninety-two children and adolescents were enrolled in a cross-sectional study. The MUP was diagnosed using consensus-based criteria proposed by Damanhoury et al. Group comparisons were performed using one-way ANOVA. To examine if sex, age group, nutritional status, puberty, hematological parameters, and insulin resistance were associated with MUP, we used multiadjusted logistic regression analysis with metabolic status as the dependent variable.    Results. The subject's age mean was 11 years (SD: 2.61). RDW values were significantly lower in children with metabolically unhealthy normal weight (MUNW) compared to children with metabolically unhealthy obesity (MUO) (12.33 ± 0.90 vs. 13.67 ± 0.52; p = 0.01), and in metabolically healthy obesity (MHO) compared to MUO (13.15 ± 0.53 vs. 13.67 ± 0.52; p = 0.04). In adolescents, the PLR was higher for the MHNW group, with a mean value of 152.60 (SD 62.97) compared to 111.16 (SD 44.12) for the MHO group. After adjusting for age, nutritional status, and puberty, hematological indices were not associated with MUP.   Conclusions. The study demonstrates that hematological indices are not independently associated with the metabolically unhealthy phenotype. Hematologic indices are unlikely to represent reliable biomarkers of MU phenotype in the pediatric population.